Effects of valproate on reproductive endocrine function in male patients with epilepsy: A systematic review and meta-analysis - Zhao, Shanshan; Wang, Xiaoyin; Wang, Yu; Xu, Junjie; Zhu, Gang; Zhao, Chuansheng; Teng, Weiyu (Epilepsy & behavior, 2018)
Valproate (VPA) is a broad spectrum antiepileptic drug (AED) that is generally used as a first line agent for most idiopathic and symptomatic generalized epilepsies. Many studies have indicated that AEDs cause reproductive endocrine disorders in males, but the exact etiology underpinning these dysfunctions is not clear. This meta-analysis and systematic review was intended to evaluate the effect of VPA on reproductive endocrine function in male patients with epilepsy. A literature search was performed using electronic databases up to December 2017 for eligible studies. The differences in the levels of the reproductive factors, luteinizing hormone (LH), follicle-stimulating hormone (FSH), sex hormone binding globulin (SHBG), testosterone, dehydroepiandrosterone sulfate (DHEAS), and androstenedione (ADION) in the male patients with epilepsy treated with VPA (treatment group) were compared with the those of the healthy controls (control group) by the use of the Standardized mean difference (SMD) with 95% confidence intervals (CIs). Six publications with a total of 316 subjects were identified. The result revealed that the levels of FSH (SMD = −1.33, 95% CI: −2.60 to −0.07, P = 0.039) and testosterone (SMD = −0.45, 95% CI: −0.87 to −0.03, P = 0.038) of the treatment group were decreased significantly compared with the healthy controls. There was an increase in the levels of SHBG (SMD = 0.41, 95% CI: −0.21 to 1.03, P = 0.197), DHEAS (SMD = 0.20, 95% CI: −0.06 to 0.45, P = 0.126) and ADION (SMD = 0.73, 95% CI: −0.10 to 1.57, P = 0.086), and a decrease in that of LH(SMD = −0.71, 95% CI: -1.49 to 0.07, P = 0.075) in the male patients with epilepsy treated with VPA, but the differences did not reach statistical significance (P > 0.05). This meta-analysis indicates that VPA may lead to a significant decrease in the levels of FSH and testosterone and alter the concentrations of LH, DHEAS, SHBG, and ADION to some extent, which might contribute to the reproductive endocrine dysfunction in male patients with epilepsy. It is important for clinical neurologists to be cautious when prescribing VPA to reproductive-aged male patients with epilepsy. •VPA decreases the levels of FSH and testosterone in male patients with epilepsy.•VPA might disturb male reproductive function by altering some reproductive factors.•Neurologists should be cautious when prescribing VPA for male patients with epilepsy.